Early Spiritualist Discussions About the Distortions of Mediumistic Communications - Alvarado, Carlos S. (Journal of Scientific Exploration, 2020)
This is a short note presenting examples of mention of distortion of mediumistic communications published by early spiritualists. it is argued that spiritualists were pioneers in discussing this issue, something that should be recognized.